2017
DOI: 10.1080/17461391.2017.1297489
|View full text |Cite
|
Sign up to set email alerts
|

Individualised dietary strategies for Olympic combat sports: Acute weight loss, recovery and competition nutrition

Abstract: Olympic combat sports separate athletes into weight divisions, in an attempt to reduce size, strength, range and/or leverage disparities between competitors. Official weigh-ins are conducted anywhere from 3 and up to 24 h prior to competition ensuring athletes meet weight requirements (i.e. have 'made weight'). Fighters commonly aim to compete in weight divisions lower than their day-to-day weight, achieved via chronic and acute manipulations of body mass (BM). Although these manipulations may impair health an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
105
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(117 citation statements)
references
References 74 publications
6
105
0
6
Order By: Relevance
“…While grappling sports like judo and wrestling involve the manipulation of an opponent's body mass, striking sports like TKD and boxing consist of techniques based on one's own body mass movement. So in these sports where specific techniques for scoring are not necessary to move or displace the opponent's body, perhaps a different body mass between athletes is not the main distinctive characteristic (Reale et al, 2016(Reale et al, , 2017. In addition, studies like that by Estevan et al (2012) and Falcó et al (2011) reported that athletes of different official weight divisions do not generate impact forces which are significantly different.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…While grappling sports like judo and wrestling involve the manipulation of an opponent's body mass, striking sports like TKD and boxing consist of techniques based on one's own body mass movement. So in these sports where specific techniques for scoring are not necessary to move or displace the opponent's body, perhaps a different body mass between athletes is not the main distinctive characteristic (Reale et al, 2016(Reale et al, , 2017. In addition, studies like that by Estevan et al (2012) and Falcó et al (2011) reported that athletes of different official weight divisions do not generate impact forces which are significantly different.…”
Section: Resultsmentioning
confidence: 99%
“…This weight categorizing is very common in most types of combat sports and martial arts, with the aim that athletes compete against opponents with similar physical characteristics, making the fights more equitable. However, combat sports athletes usually aspire to fight in a lighter weight category than their normal weight during the training period, in order to get some advantage over their opponents in terms of body mass, size, strength, and agility (Franchini, Brito, & Artioli, 2012;Kazemi, Rahman, & De Ciantis, 2011;Langan-Evans, Close, & Morton, 2011;Reale, Slater, & Burke, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We herein argue that rapid Weight loss clearly meets all three criteria and, therefore, should be banned from the sport [42], Considering that these health-threating methods are more commonly used by lower level athletes, specific education programs should be directed to them [43]. In a recent review, Fagerberg [44]discussed the negative consequences of restricting calories too severely, [45] this review summarises guidelines for athletes and coaches for manipulating BM and optimising post weigh in recovery period, also to achieve better health and performance outcomes across the different Olympic combat sports.…”
Section: Discussionmentioning
confidence: 95%